Resonance energy transfer study using a rhenium metal–ligand lipid conjugate as the donor in a model membrane - Li, Li (Chem Phys Lipids, 1999)
We measured steady state and time-resolved resonance energy transfer between donors and acceptors in model membranes. The donor was a long lifetime rhenium–lipid complex, which displayed a mean lifetime of 1 μs and lifetime components as long as 3 μs in the labeled DOPC membranes. The transfer efficiencies were found to be substantially larger than those predicted without consideration of lateral diffusion. The larger transfer efficiencies are consistent with a mutual lateral diffusion coefficient in the membrane near 2 × 10(−8) cm(2)/s. These results demonstrate that lateral diffusion in membranes can be detected with μs lipid probes.